MORFOFUNCTIONAL CARACTERISTICS OF PEOPLE WHO EXERCISE IN GYMS IN GUARAPUAVA-PR (Fiep Bulletin - online, 2013)
Today, in our city, the demand for gyms is still small, as they are not the first option when it comes to practicing physical exercises in Guarapuava-PR. People who train in gyms in Guarapuava have different reasons for exercising and different morphological and functional profiles. The purpose of this study was to evaluate morphofunctional profile of who exercise in gyms in Guarapuava-PR. The sample consisted of 100 subjects, 50 male and 50 female, aged between 20 and 30 years complete, divided proportionally among the academies of the city. They were analyzed in relation to body mass index - BMI, body fat and lean mass, flexibility, power and upper abdominal members. The results showed that body fat is high in both genders, but significantly higher among women, the flexibility of the subjects was below average for both men and women and muscle strength of upper-body was above average for both genders. It is suggested that academies pay attention to the variables body fat and flexibility in an attempt to improve the components of physical fitness.
Keywords: physical evaluation; gym; body composition